komunikasi Dokter - pasien - Alfitri Alfitri (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
Mistakes in understanding the meaning of medical symbols result in negative impact for the patients. Futhermore, it can cause malpractice. Therefore, communication between a doctor and a patient is very essential to observe. It is because some malpractices occur due to miscommunication. Disease diagnosis through patient-doctor communication is influenced by the some understanding toward the messages. It creates an effective communication. Gap in communication between a docter and a patient can cause misunderstanding as well as misinformation for the patient on his disease. The hesitation of a doctor to inform the patient on the disease well in order to prevent emotional action of the patient and his family.